Wissenschaftliches Publizieren. Zwischen Digitalisierung, Leistungsmessung, Ökonomisierung und medialer Beobachtung - Weingart, Peter (De Gruyter, 2016)
Academic publishing has been changing dramatically. The key aspects of this transformation are digitalization, economization, the concentration of the publishing industry, the introduction of performance indicators, and the development of open access models. This volume compiles relevant research findings of the Berlin-Brandenburg Academy of Sciences working group "Future of academic communication systems".